1997
DOI: 10.1074/jbc.272.28.17431
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelet-activating Factor-dependent Transacetylase in the Biosynthesis of 1-Acyl-2-acetyl-sn-glycero-3-phosphocholine by Stimulated Endothelial Cells

Abstract: Acyl analogs of platelet-activating factor (PAF) (1-acyl-2-acetyl-sn-glycero-3-phosphocholine, acylacetyl -GPC) are the predominant products synthesized during thrombin or ionophore A23187-mediated activation of endothelial cells. However, the biosynthetic pathway responsible for the production of acylacetyl-GPC is not well understood. In the present investigation, we have demonstrated that the acyl analogs of PAF are also the major products from calf pulmonary artery endothelial cells in response to a time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 57 publications
(28 reference statements)
0
30
0
Order By: Relevance
“…2B). Since the TA L strongly contributes to the acyl-PAF biosynthesis in activated EC (9), these data indicated that during induced oxidative stress, the activation of AT is predominant and that TA L scarcely contributes to the acyl-PAF biosynthesis.…”
Section: H 2 O 2 Modifies Paf Metabolismmentioning
confidence: 90%
See 4 more Smart Citations
“…2B). Since the TA L strongly contributes to the acyl-PAF biosynthesis in activated EC (9), these data indicated that during induced oxidative stress, the activation of AT is predominant and that TA L scarcely contributes to the acyl-PAF biosynthesis.…”
Section: H 2 O 2 Modifies Paf Metabolismmentioning
confidence: 90%
“…The LDL susceptibiliy to oxidative modifications can be decreased by acyl-PAF, (8) an acyl analog of PAF (1). Acyl-PAF is the predominant component produced by activated EC, and the TA L contributes to its biosynthesis (9,10). The inhibition of LDL oxidation is a well-characterized process that includes effects on the concentration or reactivity of oxidants capable of modifying LDL and on the susceptibility or resistance of LDL to these oxidants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations